Double Postbulbar Block in the Prevention of Postmanipulation Pancreatitis - P. A. Frolov; A. G. Korotkevich (Неотложная медицинская помощь, 2024)
Abstract The problems of preventing postmanipulation pancreatitis (PMP) remain the subject of debate and a lot of research from leading scientific clinics around the world. The article is devoted to the assessment of prevention methods of PMP in patients with lesion of the pancreaticobiliary zone who underwent transpapillary interventions. Aim of the study Evaluation of the effectiveness of the author’s method of preventing PMP.Material and methods A prospective two-center randomized study included 545 patients treated in the Department of Liver Surgery and General Surgery in 2020–2022, who underwent ERCP and endoscopic papillosphincterotomy. There were 146 (26.8%) male patients, and 399 (73.2%) female patients, aged from 18 to 92 years, the mean age 62.7±7.4 years. Patients were divided into 3 groups according to the method of preventing PMP: in the 1st group, standard drug premedication was supplemented with two postbulbar blocks with a solution of lidocaine 0.5% 10 ml before and after the intervention (RF Patent No. 2779221, 09/05/2022), in the 2nd group standard premedication was combined with placebo was used, and in the comparison group 3 no submucosal injections were performed. The monitoring of clinical manifestations of PMP and the level of amylase was carried out every 12 hours until the parameters normalized. Statistical processing was carried out using program STATISTICA 6.1 for Windows.Results The frequency of mild pancreatitis, corresponding to the criteria for PMP, did not exceed 18% in groups 1 and 3 (p=0.3408), but was lower with pseudo postbulbar block, 9% (χ2=2.83, р=0.0926), the difference was not statistically significant. The incidence of severe pancreatitis was significantly lower in group 1 with double postbulbar block where there were no cases of pancreatic necrosis among 143 patients (χ2=6.19, р=0.0129). The mortality did not differ significantly among groups (χ2=0.15, р=0.7004). The duration of the hospital period had significant differences between groups (Student’s t-test 1.973, p=0.001). The hospital period with double postbulbar block turned out to be significantly shorter.Conclusion 1. Double postbulbar blockade significantly reduces the risk of developing severe postmanipulation pancreatitis, regardless of existing risk factors. 2. Double postbulbar block significantly reduces the duration of the hospital period after endoscopic papillosphincterotomy. 3. Pseudo postbulbar block using saline requires further evaluation as a possible way to prevent mild pancreatitis.